Monitoring and reactive-transport modeling of the spatial and temporal variations of the Strengbach spring hydrochemistry. (15th March 2018) - Ackerer, J.; Chabaux, F.; Lucas, Y.; Clément, A.; Fritz, B.; Beaulieu, E.; Viville, D.; Pierret, M.C.; Gangloff, S.; Négrel, Ph.
Abstract: This study focuses on 20 years of hydrochemical monitoring of the small springs that emerge in the experimental granitic catchment of Strengbach (OHGE, France) and the simulation of these data using the KIRMAT code. The data indicate that the Strengbach springs display chemostatic behavior; that is, limited temporal variations were noted in the concentrations of dissolved silica (H4 SiO4 ) and most of the basic cations during the studied period (1987–2010), resulting in relative stability of the global weathering fluxes exported by the springs. Only the Ca 2+ concentrations reflect a significant decrease in all the Strengbach springs since 1987, and the variations differ from one spring to another. The modeling results show that the decrease in Ca 2+ in the Strengbach springs is due to the response of the water-rock interactions within the bedrock to the variations in the chemical composition of the soil solutions, which were characterized by a significant increase in pH and a decrease in Ca 2+ concentrations between 1987 and 2010. The decrease in Ca 2+ concentrations seen in the Strengbach springs is controlled by changes in the apatite dissolution rate and the compositions of clay minerals induced by the soil solution changes. The differences observed between the Ca 2+ trends of the springs are related to changes in the residence time of the water supplying the different springs. The weak impact of the soil solution modifications on the dissolution rates of other primary minerals and on the bulk precipitation rates of the clay minerals explains the relative stability over time of the concentrations of the other cations and dissolved silica in the water derived from the Strengbach springs. Further, the hydrochemical simulations suggest that the chemostatic behavior of the Strengbach springs cannot be explained by the mobilization of waters that are close to chemical equilibrium, but rather by a hydrological control of the spring water residence times. Finally, a comparison of current and long-term weathering rates determined from the spring water monitoring and a regolith profile shows that the modern chemical fluxes of Ca 2+ are higher than the long-term ones, whereas the weathering fluxes of H4 SiO4 and Na + have likely been much more stable over time. All of these results indicate that the silicate weathering processes are characterized by weak spatial and temporal variability in the Strengbach catchment, while the chemical elements such as Ca 2+, for which the budget in the spring waters is controlled by the dynamic behavior of clay minerals and minor minerals such as apatite, are significantly affected by Quaternary climatic variations and decennial environmental changes.